Religion and ethics among academics: a work of heart? / Naqiah Awang, Nur Syafiqah Hussin and Nurul Afzan Najid - Awang, Naqiah; Hussin, Nur Syafiqah; Najid, Nurul Afzan (2016)
Being an academic has always being connected to continuous rewards in hereafter that whoever teaches some knowledge will have the reward of the one who acts upon it, without detracting from his reward in the slightest. Meanwhile, previous literatures prove that religion contributes to one's ethical behavior that it serves as a boundary of what is right or wrong. Having these two elements of religion and ethics embedded in oneself, this study will elicit the effect towards career management behavior of academics. Academics are the lifeblood of an education institution since they are obligated to shape the future generation. Being a role model to students, learning through exemplary is as important as the knowledge they delivered. Therefore, it is so important to investigate what drives them to treat this noble profession as one of their primacy of life fulfillment. As such, this study reviews literatures pertaining to the mutual importance of ethical value and religion on academic's career management behavior.